Edukasi Manajemen Osteoarthritis Knee pada Ibu-Ibu Petani Prancak, Pasongsongan, Sumenep, Madura - Arys Hasta Baruna; Faiqatul Qari'ah (Health Care : Journal of Community Service, 2026)
This community service activity aimed to improve knowledge and awareness among female farmers in Prancak Village, Pasongsongan, Sumenep, regarding knee osteoarthritis (KOA) management through health education and simple stretching exercises. This topic was chosen due to the high incidence of knee pain among farmers performing repetitive and squatting tasks. The activity was conducted in one day with three stages: a pretest using the WOMAC questionnaire, education and stretching exercise practice, and a posttest. Results showed a decrease in WOMAC scores, indicating improvement in pain, stiffness, and knee function; mild category increased from 13% to 40%, while severe category decreased from 33% to 7%. The activity proved effective in reducing knee complaints and enhancing awareness of ergonomic working posture. This short-term program can serve as a sustainable model for community-based osteoarthritis education with support from local health workers and village authorities.